Palynology of Amicia Kunth. (Leguminosae–Papilionoideae–Dalbergieae–Informal Adesmia clade) set in a systematic and phylogenetic context - Antonio-Domingues, Higor; Fortuna-Perez, Ana Paula [UNESP]; Rossi, Mônica Lanzoni; Martinelli, Adriana Pinheiro; Lewis, Gwilym Peter; Pinto da Luz, Cynthia Fernandes (Taylor & Francis, 2022)
Amicia is the least diverse genus of the Adesmia clade. It has a disjunct distribution with six endemic species restricted to the central Andes of South America and one species endemic to Mexico. The phylogeny and taxonomy of this genus have been extensively studied. Nevertheless, pollen data are still insufficiently known within a taxonomic context. In this study, we analysed all Amicia species using light, scanning, and transmission electron microscopy and we present phylogenetically useful palynological information to support taxonomic studies. Variation in pollen grain size and aperture features is used to delimit pollen types, which corroborate molecular and biogeographical data. Multivariate analysis reinforced the pollen type subdivisions and revealed novel diagnostic morphological features for two infrageneric taxa of Amicia. Our pollen results provide informative pollen characters to assist in the delimitation of Amicia species, which can be easily misidentified due to similarities in vegetative structures. Amicia pollen morphology reflects population isolation and divergence of Amicia lineages and provides critical features for future phylogenetic optimisation of the Adesmia clade.
Keywords: Central America; Dalbergia clade; Fabaceae; Mexico; pollen morphology; South America; ultrasculpture; ultrastructure